Comparison of risk stratification scoring system as a predictor of mortality and morbidity in congenital heart disease patients requiring surgery - Dicky Fakhri; Ni Made Ayu Sintya Damayanti; Muhammad Nurhanif (Wolters Kluwer Medknow Publications, 2023)
Backgrounds : Risk stratification systems have been important in reducing morbidity and mortality among congenital heart disease (CHD) patients requiring cardiac surgery. Multiple risk stratification scoring systems have been developed, including Aristotle Basic Complexity Score (ABC), Aristotle Comprehensive Complexity Score (ACC), Society of Thoracic Surgeons and European Association for Cardiothoracic Surgery (STS-EACTS), and Risk Adjustment in Congenital Heart Surgery (RACHS-1). This study aims to access the superior risk stratification scoring system model in predicting mortality and morbidity. Methods : The authors used Embase, PubMed, Scopus, and ProQuest as the primary databases for searching and included studies from hand searching. The area under the receiver operating characteristic curve was compared. Results : A total of 11 articles were included in this review. The AUC of ABC for predicting mortality ranges from 0.59 to 0.71, and morbidity ranges from 0.673 to 0.743. The AUC of ACC score for predicting mortality ranges from 0.704 to 0.87, and a study revealed the AUC of morbidity is 0.730. The AUC of RACHS-1 for predicting mortality ranges from 0.68 to 0.782. The AUC of STS-EACTS for predicting mortality ranges from 0.739 to 0.8 and 0.732 for predicting morbidity. Conclusion : ABC, ACC, RACHS-1, and STS-EACTS have acceptable to excellent discriminatory ability in predicting mortality and morbidity among CHD patients requiring cardiac surgery.